Pengaruh Lingkungan Kerja, Disiplin Kerja dan Kemampuan Kerja Terhadap Peningkatan Kompetensi Guru pada SMK Katolik Muktyaca Ende - Maria Serafina Kewa; Rafael Octavianus Byre; Hyronimus Se (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to determine: 1) The influence of work ability on increasing teacher competency at Muktyaca Ende Catholic Vocational School. 2) The influence of motivation on increasing teacher competency at Muktyaca Ende Catholic Vocational School. 3) The influence of work ability on increasing teacher competency at Muktyaca Ende Catholic Vocational School. This research is quantitative research, the sample in this research is all teachers who work at Muktyaca Ende Catholic Vocational School, totaling 43 people. Data collection techniques are carried out by means of observation, questionnaires and documentation. Results of statistical tests on the influence of the work environment (X1) on increasing teacher competency at Muktyaca Ende Catholic Vocational School (Y) of 5.487>1.684 and a significant value of 0.000 <0.05 has an effect on increasing teacher competency. Statistical test of the influence of work discipline (X2) towards increasing the competency of the Muktyaca Ende Catholic Vocational School (Y) of 6.829 > 1.699 and a significant value of 0.000 < 0.05 has an effect on increasing teacher competency. Statistical test of the influence of work ability (X3) towards increasing teacher competency at Muktyaca Ende Catholic Vocational School (Y) of -0.470 < 1.684 and a significant value of 0.642 > 0.05 was stated to have no effect on increasing teacher competency.